Conservação de ecossistemas lacustres em Santarém, Amazônia oriental paraense: desafios e perspectivas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
Amazonian lakes play an important role in maintaining biodiversity, being endowed with social, economic and territorial relevance, and when located in or near urban centers, they are subject to several impacts. Thus, with the objective of evaluating the environmental conditions of flood lakes, located in an urban expansion area of the municipality of Santarém, Pará, and subject to different anthropic actions, the following specific objectives were established: 1) to understand the economic and socio-environmental dynamics that are established according to lake ecosystems, located in urban expansion areas of the municipality of Santarém, western Pará State; 2) to study the relationship between Environmental Protection Areas (EPAs) and the conservation of lake ecosystems in the municipality of Santarém, from the perspective of the Tapari and Juá flood lakes related to the Alter do Chão and Juá APAs, respectively; 3) to analyze the concentration of nutrients and water quality in the floodplain lakes of the Tapajós, Tapari and Juá river basins in comparison with the standards established by CONAMA Resolution n° 357/2005 for water bodies, class 2, by physical-chemical and microbiological variables; 4) to produce a visual essay on the studied lake ecosystems. To this end, bibliographic, documentary and qualitative research were carried out; analysis of cartographic data; photographic records; and analysis of limnological variables of water samples collected monthly between January and December of 2021, encompassing the flood, high water, ebb and low water periods of the Tapajós River. The results indicate that despite the changes in the landscape and the deterioration of existing resources and natural capital, the lakes are resilient to human actions and lack responsible and active management, without separating environmental impacts from socioeconomic, political and cultural impacts. Both the biophysical and artificial environments should be evaluated and monitored. Lake ecosystems are important sources of natural capital for the maintenance of life and environmental quality. It is essential to keep them in good conservation conditions in order to avoid their transformation into critical natural capital.
Keywords: Políticas Públicas; Qualidade Ambiental; Recursos Hídricos; CNPQ:: CIENCIAS AMBIENTAIS